Higher education institution Wi-Fi network vulnerabilities: a multiple case study (Research, Society and Development, 2020)
Along with Wi-Fi networks, which are on the rise in today's information age, new risks have also emerged for users and higher education institutions providing such networks. The objective of this study was to analyze, through a Penetration Test (Pentest), the vulnerabilities and threats present in the Wi-Fi networks of Higher Education Institutions (HEIs) of Belo Horizonte and of cities in the interior of Minas Gerais near the capital. . Data collection was performed through experimental testing - Pentesting in loco - in Wireless Local Area Network (WLAN) of the 12 participating Higher Education Institutions. The results showed that IES Wi-Fi network infrastructure is very diverse and that a significant percentage of these WLANs are vulnerable and may be threatened by malicious users.